2012
DOI: 10.1128/iai.00620-12
|View full text |Cite
|
Sign up to set email alerts
|

The Asd + -DadB + Dual-Plasmid System Offers a Novel Means To Deliver Multiple Protective Antigens by a Recombinant Attenuated Salmonella Vaccine

Abstract: We developed means to deliver multiple heterologous antigens on dual plasmids with non-antibiotic-resistance markers in a single recombinant attenuated vaccine strain of Salmonella enterica serotype Typhimurium. The first component of this delivery system is a strain of S. Typhimurium carrying genomic deletions in alr, dadB, and asd, resulting in obligate requirements for diaminopimelic acid (DAP) and D-alanine for growth. The second component is the Asd ؉ -DadB ؉ plasmid pair carrying wildtype copies of asdA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…The DadB + vector can be used either alone (in a Δ alr Δ dadB mutant) or in conjunction with an Asd + plasmid (in a Δ asdA Δ alr Δ dadB triple-mutant strain) in S . Typhimurium to deliver multiple antigens (see below) [115]. …”
Section: Recombinant Antigen Synthesis and Deliverymentioning
confidence: 99%
See 3 more Smart Citations
“…The DadB + vector can be used either alone (in a Δ alr Δ dadB mutant) or in conjunction with an Asd + plasmid (in a Δ asdA Δ alr Δ dadB triple-mutant strain) in S . Typhimurium to deliver multiple antigens (see below) [115]. …”
Section: Recombinant Antigen Synthesis and Deliverymentioning
confidence: 99%
“…Our initial constructions showed that there was an inverse correlation between the amount of DadB produced for complementation of the Δ alr Δ dadB mutant when using DadB + vectors with different copy numbers and this attenuated the virulence of vaccine strains [115]. It was reported that low-copy-number plasmids are relatively more stable and induce greater levels of antigen-specific immune responses than their high-copy-number versions [121].…”
Section: Recombinant Antigen Synthesis and Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Encoding several foreign antigens on a single expression plasmid may lead to unacceptably large and unstable plasmids which spontaneously delete the desired coding regions, thereby compromising immune specificity (26,27). The use of several compatible plasmids for antigen expression in a single live vector vaccine may exacerbate the metabolic burden and again overattenuate the vaccine strain, leading to plasmid loss in the absence of selection (28). Finally, administration of several vaccine strains encoding individual antigens cannot guarantee equivalent antigen delivery from all strains, again potentially interfering with immune responses (29).…”
mentioning
confidence: 99%